GLP-1 receptor agonism ameliorates hepatic VLDL overproduction and de novo lipogenesis in insulin resistance - Jennifer Taher; Christopher L. Baker; Carmelle Cuizon; Hassan Masoudpour; Rianna Zhang; Sarah Farr; Mark Naples; Celine Bourdon; Zdenka Pausova; Khosrow Adeli (Elsevier, 2014)
Background/objectives: Fasting dyslipidemia is commonly observed in insulin resistant states and mechanistically linked to hepatic overproduction of very low density lipoprotein (VLDL). Recently, the incretin hormone glucagon-like peptide-1 (GLP-1) has been implicated in ameliorating dyslipidemia associated with insulin resistance and reducing hepatic lipid stores. Given that hepatic VLDL production is a key determinant of circulating lipid levels, we investigated the role of both peripheral and central GLP-1 receptor (GLP-1R) agonism in regulation of VLDL production. Methods: The fructose-fed Syrian golden hamster was employed as a model of diet-induced insulin resistance and VLDL overproduction. Hamsters were treated with the GLP-1R agonist exendin-4 by intraperitoneal (ip) injection for peripheral studies or by intracerebroventricular (ICV) administration into the 3rd ventricle for central studies. Peripheral studies were repeated in vagotomised hamsters. Results: Short term (7-10 day) peripheral exendin-4 enhanced satiety and also prevented fructose-induced fasting dyslipidemia and hyperinsulinemia. These changes were accompanied by decreased fasting plasma glucose levels, reduced hepatic lipid content and decreased levels of VLDL-TG and -apoB100 in plasma. The observed changes in fasting dyslipidemia could be partially explained by reduced respiratory exchange ratio (RER) thereby indicating a switch in energy utilization from carbohydrate to lipid. Additionally, exendin-4 reduced mRNA markers associated with hepatic de novo lipogenesis and inflammation. Despite these observations, GLP-1R activity could not be detected in primary hamster hepatocytes, thus leading to the investigation of a potential brain-liver axis functioning to regulate lipid metabolism. Short term (4 day) central administration of exendin-4 decreased body weight and food consumption and further prevented fructose-induced hypertriglyceridemia. Additionally, the peripheral lipid-lowering effects of exendin-4 were negated in vagotomised hamsters implicating the involvement of parasympathetic signaling. Conclusion: Exendin-4 prevents fructose-induced dyslipidemia and hepatic VLDL overproduction in insulin resistance through an indirect mechanism involving altered energy utilization, decreased hepatic lipid synthesis and also requires an intact parasympathetic signaling pathway.